2017
DOI: 10.1111/jphp.12745
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between E2F1 and P53 transcription factors in doxorubicin-induced DNA damage: evidence for preventive/protective effects of silymarin

Abstract: DOX-induced testicular toxicity was characterized by lowering sperm quality values, induction of oxidative and nitrosative stress and DNA fragmentation. Preventive and protective effects of SMN on DOX-induced testicular toxicity may attribute to its antioxidant property. DOX-induced testicular damages and SMN preventive/protective effects might be mediated via up- and down-regulation of p53 and E2F1 transcription factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…These combinations were evaluated in their anti-oxidant and anti-inflammatory capacity; according to our results, two combinations (M4 and M5) exhibited anti-inflammatory effects (decreased IL-6 levels, Fig. 7A) and anti-oxidant effects (decreased O 2 • − levels) similar to those of silymarin, a flavonoid with well-documented anti-oxidant and anti-inflammatory activity 4446 .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These combinations were evaluated in their anti-oxidant and anti-inflammatory capacity; according to our results, two combinations (M4 and M5) exhibited anti-inflammatory effects (decreased IL-6 levels, Fig. 7A) and anti-oxidant effects (decreased O 2 • − levels) similar to those of silymarin, a flavonoid with well-documented anti-oxidant and anti-inflammatory activity 4446 .…”
Section: Discussionmentioning
confidence: 83%
“…Once adipocyte dysfunction was established as described below, five concentrations (5, 10, 20, 40, or 80 μg/mL) of the three Aq-Cs SFs (SF1, SF2, and SF3) were added to the culture and allowed to stand for 24 h. Either silymarin (50 μg/mL) 50,51 or metformin (1 mM) 52,53 were used as positive controls; previous reports have employed these molecules as standard drug: for silymarin as control of oxidative stress and the inflammatory condition induced by the presence of IL-1β 45,46 . For Metformin it was used as control of glucose consumption and the accumulation of lipids in adipocytes, functions that were affected by the presence of dexamethasone 2730 .…”
Section: Methodsmentioning
confidence: 99%
“…It has been also shown that silymarin coadministration with chemotherapeutic agents has, often, a protective effect in reducing chemotherapeutic toxicities in normal organs (Fanoudi, Alavi, Karimi, & Hosseinzadeh, ). For example, animals receiving DOX were shown to have p53 expression up‐regulated and E2F1 down‐regulated at mRNA level, which could be reserved following silymarin administration (Shafiei‐Roudbari, Malekinejad, Janbaz‐Aciabar, & Razi, ). Furthermore, silymarin significantly reduced DOX‐induced sperm abnormalities, as well as DNA fragmentation and NO concentration (Shafiei‐Roudbari et al, ).…”
Section: Silymarin Combination With Other Chemotherapeutic Agents In mentioning
confidence: 99%
“…For example, animals receiving DOX were shown to have p53 expression up‐regulated and E2F1 down‐regulated at mRNA level, which could be reserved following silymarin administration (Shafiei‐Roudbari, Malekinejad, Janbaz‐Aciabar, & Razi, ). Furthermore, silymarin significantly reduced DOX‐induced sperm abnormalities, as well as DNA fragmentation and NO concentration (Shafiei‐Roudbari et al, ). Also, it increased total antioxidant power, rate of sperm motility, and viability in animal models.…”
Section: Silymarin Combination With Other Chemotherapeutic Agents In mentioning
confidence: 99%
See 1 more Smart Citation